Análise dos documentos oficiais que versam sobre a educação infantil do/no campo em Domingos Martins à luz da pedagogia histórico-crítica - Lourenço, Kristine (2016)
This research has as objective to analyze the official documents from Domingos Martins county which talks about children schooling in the field of critic-historic education. The analyzed documents were the ones from education county from (2015-2015), the curricular document from the city’s education system (2016) and the political education project from children school called “Germano Gerhardt” - 2015. Besides that, this research is to try to establish the alignments of documents from Domingos Martins to the documents that are around the Brazilian education in a general way, taking into consideration the theorical references from the education system from “Learn how to learn”. We tried to defend that either in the school from the countryside or in the school from the city need to fight against unfair distribution of income, against the hegemonic knowledge, against the dehumanization of the human being, but in order for this to occur, we need to recognize that there is no difference between the countryside school education and city’s school education, in a generalized way which guarantees its expertise, once the individuals from the rural area and the city have the rights to have access to knowledge historically produced by humankind. Therefore, we try to contribute with the arguments considering the education processes from children around (0 to 3 years old) in the age of prekindergarten (4 to 6) forwarding children education that demystify the ideal education from "learn how to learn" that has positioned the hegemony in the Brazilian education. In this sense, the defense of historically critical education articulates the systematically from knowledge produce by humankind on the projects done in the schools and the process facing the fight in the society, understanding that the school is a space institutionalized by the socialization of knowledge very well developed that collaborates to the change of individuals